Metabolic effects of n-3 PUFA as phospholipids are superior to triglycerides in mice fed a high-fat diet: possible role of endocannabinoids - Rossmeisl, Martin; Jilkova, Zuzana Macek; Kuda, Ondrej; Jelenik, Tomas; Medrikova, Dasa; Stankova, Barbora; Kristinsson, Björn; Haraldsson, Gudmundur G; Svensen, Harald; Stoknes, Iren; Sjövall, Peter; Magnusson, Ylva; et al. (PloS one, 2012)
BACKGROUND: n-3 polyunsaturated fatty acids, namely docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), reduce the risk of cardiovascular disease and can ameliorate many of obesity-associated disorders. We hypothesised that the latter effect will be more pronounced when DHA/EPA is supplemented as phospholipids rather than as triglycerides. METHODOLOGY/PRINCIPAL FINDINGS: In a 'prevention study', C57BL/6J mice were fed for 9 weeks on either a corn oil-based high-fat obesogenic diet (cHF; lipids ∼35% wt/wt), or cHF-based diets in which corn oil was partially replaced by DHA/EPA, admixed either as phospholipids or triglycerides from marine fish. The reversal of obesity was studied in mice subjected to the preceding cHF-feeding for 4 months. DHA/EPA administered as phospholipids prevented glucose intolerance and tended to reduce obesity better than triglycerides. Lipemia and hepatosteatosis were suppressed more in response to dietary phospholipids, in correlation with better bioavailability of DHA and EPA, and a higher DHA accumulation in the liver, white adipose tissue (WAT), and muscle phospholipids. In dietary obese mice, both DHA/EPA concentrates prevented a further weight gain, reduced plasma lipid levels to a similar extent, and tended to improve glucose tolerance. Importantly, only the phospholipid form reduced plasma insulin and adipocyte hypertrophy, while being more effective in reducing hepatic steatosis and low-grade inflammation of WAT. These beneficial effects were correlated with changes of endocannabinoid metabolome in WAT, where phospholipids reduced 2-arachidonoylglycerol, and were more effective in increasing anti-inflammatory lipids such as N-docosahexaenoylethanolamine. CONCLUSIONS/SIGNIFICANCE: Compared with triglycerides, dietary DHA/EPA administered as phospholipids are superior in preserving a healthy metabolic profile under obesogenic conditions, possibly reflecting better bioavalability and improved modulation of the endocannabinoid system activity in WAT.
Keywords: Eicosapentaenoic Acid; Analysis of Variance; Male; kvantitativní polymerázová řetězová reakce; Obesity; Metabolomics; kyseliny dokosahexaenové; Fatty Acids, Omega-3; metabolomika; obezita; Microscopy; omega-3 mastné kyseliny; Muscle, Skeletal; Diet, High-Fat; imunohistochemie; mužské pohlaví; dieta s vysokým obsahem tuků; endokanabinoidy; Real-Time Polymerase Chain Reaction; triglyceridy; Endocannabinoids; bílá tuková tkáň; Body Weight; Adipose Tissue, White; modulátory kanabinoidních receptorů; kosterní svaly; biologická dostupnost; Animals; Cannabinoid Receptor Modulators; kyselina eikosapentaenová; játra; analýza rozptylu; mikroskopie; Immunohistochemistry; Phospholipids; Docosahexaenoic Acids; zvířata; myši inbrední C57BL; fosfolipidy; myši; Biological Availability; Mice, Inbred C57BL; Liver; Mice; tělesná hmotnost; Triglycerides